Contact Free Impedance Methodology for Investigating Enzymatic Reactions into Dielectric Polymer Microchip. Issue 5 (22nd February 2013) - Faure, Mathilde; Kechadi, Mohammed; Sotta, Bruno; Gamby, Jean; Tribollet, Bernard
Abstract A methodology for free contact microchannel impedance measurements through a dielectric microchip was developed for monitoring the kinetics of enzymatic reactions. For that purpose, we propose a procedure which consists of subtracting the impedance contribution of the dielectric polymer layer, which separates the two parallel microband electrodes embedded in it, from the global microchip impedance. This operation allows microchannel impedance enhancement for real time monitoring of impedance modulus changes without direct electrical contact. Application for determination of kinetic parameters of enzyme‐substrate reaction independently of optical or electrochemical properties of the substrates is demonstrated. Hydrolysis 4‐nitrophenylphosphate (pNPP) and 4‐aminophenylphosphate (pAPP), which are two substrates for Alkaline Phosphatase (ALP), are taken as examples. Moreover, signal amplification response of the impedance modulus is achieved by the use of superparamagnetic microbeads as enzyme supports. Plotting the maximum rate against the ALP concentration gives rise to straight lines with a slope that is the hydrolysis catalytic pseudo first‐order rate constant, kcat. Sensitivity, selectivity and reproducibility of these measurements have been demonstrated comparatively with both substrates. kcat values were 103 s−1 and 52 s−1 with pAPP and pNPP, respectively.